On the question of the optimal age for starting sports: results of a bibliometric analysis of the works of foreign and Russian scientists - Novikova, I. I.; Usacheva, E. V.; Zubtsovskaya, N. A.; Semenikhina, M. V. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to identify the degree of elaboration of the issue of determining the optimal age for starting sports on the basis of a bibliometric analysis of the works of foreign and Russian scientists.